2019
DOI: 10.18801/jbar.190119.193
|View full text |Cite
|
Sign up to set email alerts
|

Oil palm smallholders and certification: exploring the knowledge level of independent oil palm smallholders to certification

Abstract: Oil palm is the world leading vegetable oil. It is an important player in the economic development of the country, both as a contributor to gross national product (GDP), foreign earnings and job creation. With high yields per hectare, cheap to produce and its application to food and non-food industries makes it an important product both locally and internationally. The demand for palm oil has lead to expansion of oil palm plantation around the world over the past several decades, with Indonesia and Malaysia ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Concerning the environmental dimension, these results underscore the cooperative's initiatives on minimising the environmental impacts by recycling the oil palm waste for other purposes, and the support provided by cooperatives in obtaining oil palm sustainability certification. Nevertheless, independent smallholders have been recognised for their environmental commitment, particularly in sustainability certification (Abazue et al, 2019;Senawi, 2019). Even though each organisation is unique, SOP based on specific indicators must be relevant to its operations and boundaries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the environmental dimension, these results underscore the cooperative's initiatives on minimising the environmental impacts by recycling the oil palm waste for other purposes, and the support provided by cooperatives in obtaining oil palm sustainability certification. Nevertheless, independent smallholders have been recognised for their environmental commitment, particularly in sustainability certification (Abazue et al, 2019;Senawi, 2019). Even though each organisation is unique, SOP based on specific indicators must be relevant to its operations and boundaries.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the oil palm cooperatives, they play a critical role in supporting the implementation of SOP among the smallholders, although the scholarly literature on managing SOP in the oil palm cooperatives' context is still in its infancy. For instance, existing studies (Abazue et al, 2015(Abazue et al, , 2019Ador et al, 2016;Begum et al, 2018;Choy & Albanya, 2017;Umaira et al, 2017) have been found to debate on the sustainability of oil palm smallholders in Malaysia which is grounded around the Elkington's (1998) approach. Among those studies, one study included conceptual and reviewed studies based upon secondary data (Ador et al, 2016), three studies conducted the data analysis using a descriptive statistic, and frequency count without emphasising on reliability and validity of the measurement indicators and sustainability construct (Abazue et al, 2015;Begum et al, 2018;Umaira et al, 2017) and one study confines its focus to one specific dimension of sustainability (Choy & Albanya, 2017).…”
Section: Theoretical Basis Of Sustainability-oriented Practices (Sop) Constructmentioning
confidence: 99%
“…However, compliance to the MSPO requirement is challenging to many of the millers, since in order to be certified, a certain set of new equipment such as scrubbers, biogas capture, and treatment devices has to be bought and installed in the plant. Besides monetary issues, the knowledge gap is also critical among the millers especially the smaller independent establishments [68][69][70]. Many of them have never invested in R&D, and therefore are not well informed of technology advancements in the oil extraction and/or renewable power generation (in this case biogas and biomass), nor do they have good access to industry experts and a proper technology transfer hub.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…In order to promote energy efficiency and consumption of alternative fuels, new incentive mechanisms should be structured to encourage utilities to strengthen energy system performance and upgrade infrastructure. Likewise, in order to further promote bio-CNG consumption in the transportation sector, the government could include the provision of mandatory use of bio-CNG, such as implemented on B5 biodiesel blend mandated in the Malaysian Biofuel Industry Act 2007 [68]. c Adaptation of mandatory biomass inventory and sustainability monitoring into MSPO: The current MSPO still lacks more specific requirements with regard to proper disposal of waste [100].…”
Section: Table 6 Power Generation Potential Of Palm Oil Biomass (Mw)mentioning
confidence: 99%
“…Low FFA of CPO for export commodity coming from the plantation owned by big enterprises. Meanwhile, Indonesia's smallholder only contributes about 3% of 9% of the export value of smallholders worldwide [2]. Low FFA of CPO for export comprises premium-grade with less than 2% of FFA content and super-grade with less than 3.5% of FFA content.…”
Section: Introductionmentioning
confidence: 99%